Assessing the effect of different shapes of glyco-gold nanoparticles on bacterial adhesion and infections - Chaudhary, Preeti Madhukar; Sangabathuni, Sivakoti; Murthy, Raghavendra Vasudeva; Paul, Ajay; Thulasiram, Hirekodathakallu V.; Kikkeri, Raghavendra (Chemical Communications, 2015)
Achieving selective and sensitive carbohydrate-protein interactions (CPIs) using nanotechnology is an intriguing area of research. Here we demonstrate that the different shapes of gold nanoparticles (AuNPs) functionalized with monosaccharides tune the bacterial aggregations. The mechanism of aggregation revealed that the large number of surface interactions of rod shaped mannose-AuNPs with E. coli ORN 178 compared with spherical and star-shaped AuNPs exhibited higher avidity and sensitivity. Moreover, such sensitive binding can be used for effective inhibition of bacterial infection of cells.

Supramolecular scaffolds on glass slides as sugar based rewritable sensors for bacteria - Gade, Madhuri; Paul, Ajay; Alex, Catherine; Choudhury, Devika; Thulasiram, Hirekodathakallu V.; Kikkeri, Raghavendra (Chemical Communications, 2015)
We describe here the sugar functionalized beta-cyclodextrin-ferrocene glass slides as fully reversible bacterial biosensors under the influence of external adamantane carboxylic acid. The prototype D-mannose - E. coli ORN 178 and L-fucose - P. aeruginosa interactions serve as a model to illustrate the new approach.

Lipase catalyzed synthesis of antimicrobial andrographolide derivatives - Patil, Harshal S.; Jadhav, Dipesh; Paul, Ajay; Mulani, Fayaj Alam; Karegaonkar, Shrikant J.; Thulasiram, Hirekodathakallu V. (Data in Brief, 2018)
In this data article we describe screening of various lipases for the regioselective acylation of Andrographolide. Each lipase was screened with seven acyl donors. Amano lipase AK from Pseudomonas fluorescens was used for the synthesis of two new acylated andrographolide derivatives. Two new compounds, andrographolide-14-propionate and andrographolide-14-caproate were characterized by various spectral studies. These two derivatives showed more antimicrobial activity than andrographolide.

Regioselective and efficient enzymatic synthesis of antimicrobial andrographolide derivatives - Patil, Harshal S.; Jadhav, Dipesh D.; Paul, Ajay; Mulani, Fayaj A.; Karegaonkar, Shrikant J.; Thulasiram, Hirekodathakallu V. (Bioorganic & Medicinal Chemistry Letters, 2018)
Labdane diterpene andrographolide (1) is a major constituent of Andrographis paniculata and known to exhibit wide spectrum of biological activities. In this study, regioselective monoesters of (1) have been synthesized by using Amano lipase AK (Pseudomonas fluorescens) as a biocatalyst. Amano lipase AK was able to execute highly efficient esterification of hydroxyl group attached to C-14 carbon of (1) in presence of acyl donors. Among the various synthesized derivatives including two novel compounds such as andrographolide-14-propionate (3) and andrographolide-14-caproate (5) displayed antimicrobial activity against Staphylococcus aureus with low minimal inhibitory concentration (MIC) 4 mu g/mL and 16 mu g/mL respectively. Furthermore, they have shown low hemolysis activity at their respective MIC and increase in the permeability of the bacterial cell membrane as delineated by FITC uptake and SEM imaging studies. (C) 2018 Elsevier Ltd. All rights reserved.
Keywords: Acylation; Andrographolide; Antimicrobial activity; biocatalysis; Hemolysis; Lipase; Natural product